6 MV wedge photon beam profiles with the fricke xylenol gel dosimeter - Oliveira,Lucas N. de (2009)
Wedged beam are often used in clinical radiotherapy to compensate missing tissues and dose gradients. In this work, the Fricke Xylenol Gel (FXG) dosimeter was used for 6 MV photons radiation wedge field profiles measurements, allowing to infer the wedge filter physical attenuation coefficient. This dosimeter is a chemical system of a Fe3+-Xylenol complex concentration, that when measured spectrophotometrically, the absorbance is directly proportional to the absorbed dose. From theses results one can infer that the FXG can be used also as an alternative dosimetric system for measurements of wedge filters.